ІДЕНТИФІКАЦІЯ ДЖЕРЕЛ КАПІТАЛУ БРЕНДУ РОЗДРІБНОГО РИНКУ НАФТОПРОДУКТІВ НА ОСНОВІ «ДНК»-ПІДХОДУ - Малинка, О. Я.; Устенко, А. О. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
A comprehensive analysis of the sources of capital formation of the brand of the retail market of light oil products on the basis of a "DNA" approach has been carried out. As a result, a number of tools and methods have been identified with which it is possible to evaluate the effect of individual components of brand identity (associations, image, individuality, location, perceived quality, value and core) on a particular market segment. To evaluate the effect of individual components of the OKKO brand, it is suggested to use such tools and methods: survey and observation, expert assessments, arbitrary associations, detailed questions, scales, brand perception mapping, brand mapping, subjective brand classification analysis, visual perception mapping goods, EquiTrend, the construction of maps for determining the nominal value of the brand and the matrix for the deployment of quality functions, testing the perception and recognition of brand attributes, testing ease of remembering brand loyalty to the brand testing, testing the possibility of replacing the brand. After all, it is important for the company to assess the consumer perception of the brand (to analyze the impact of its identity components on consumer impressions of contact with the product) in order to achieve the maximum coincidence of the planned and perceived brand content. To do this, it is needed to have a full understanding of how consumers buy and use the goods, and most importantly - about what they know, how think and feel. Keywords: brand, brand equity, "DNA"-approach to brand building, oil retail market.